Pore supercritical foaming PET (polyethylene terephthalate) material and preparation method thereof

Through the combination of nanonucleation agent, surfactant and crystallization accelerator, combined with multi-stage foaming agent technology, the problems of uneven dissolution and slow crystallization rate of PET foaming materials in high-temperature processing are solved, and fine pores are achieved The high foaming ratio and mechanical performance of PET materials are suitable for the wind power industry.

CN119161702APending Publication Date: 2024-12-20ANHUI DONGYUAN NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411505108.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Due to high temperature processing, the foaming agent is unevenly dissolved, low melt viscosity and slow crystallization rate, resulting in limited foaming rate, large cell size, low cell density and insufficient mechanical properties, which limits its inability to Application of the wind power industry.

Method used

Using a combination of nanonucleation agent, surfactant and crystallization accelerator, combined with multi-stage filling technology of supercritical carbon dioxide and alkane foaming agent, the temperature partition control of the twin-screw extrusion section is formed to form uniform small-size crystals. In order to increase the bubble nucleation rate and quantity, avoid the problem of excessive crystallization caused by supercritical CO2 saturation.

Benefits of technology

The high foaming ratio, closed cell ratio and mechanical properties of fine pore PET foaming materials have been improved. The cell size is less than 150-250μm, which significantly improves the material's load resistance and lightweight effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161702A_ABST
    Figure CN119161702A_ABST
Patent Text Reader

Abstract

The invention relates to the field of PET foaming core materials, in particular to a fine-pore supercritical foaming PET material and a preparation method thereof.The PET material is prepared from, by weight, 60-100 parts of PET and 0.5-5 parts of an organic nucleating agent; 0.1 to 0.5 part of a nano nucleating agent; 0.2 to 1 part of a surfactant; 0.5 to 1 part of a crystallization accelerant; 0.5 to 5 parts of an antioxidant; 0.5 to 5 parts of a chain extender; and 0.5-5 parts of a foaming agent. According to the invention, the organic nucleating agent, the nano nucleating agent, the surfactant and the crystallization promoter are mixed, and a multi-section filling mode of the foaming agent is combined, so that on one hand, low-temperature mixing of the foaming agent and the nucleating agent can be realized, and non-uniform dissolution of the foaming agent during high-temperature processing is avoided; the problems of low melt viscosity, low crystallization rate, low cell shaping rate and the like are solved; on the other hand, a large number of small-size crystal regions can be formed in the PET mixed melt to serve as heterogeneous nucleation points of bubbles, and finally the fine-hole PET foaming material can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of PET foam core materials, in particular to a fine-pore supercritical foamed PET material and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate (PET) is a semi-crystalline linear macromolecular material with a high melting point, good mechanical properties, electrical insulation, creep resistance and many other advantages. At present, PET foam materials have great room for improvement and application prospects in the field of wind power core materials at home and abroad due to their advantages in weight and mechanical properties. Among them, the foaming ratio and pore size of PET foam materials are particularly important as apparent indicators for measuring the lightweight and mechanical properties of PET foam materials. At present, conventional PET foam materials have disadvantages such as uneven dissolution of foaming agents, low melt viscosity, slow crystallization rate, and slow shaping rate of pores due to high-temperature processing. The prepared foamed PET materials have limited foaming ratios, large pore sizes, and low pore density, resulting in a large room for improvement in the mechanical properties of the final foamed products. The pore size and density of PET foam materials greatly affect the effect of the back-end application of PET materials. In the wind power industry where PET foam materials are used, fine-pored PET materials can reduce the absorption of resin during processing, reduce the weight of blades, and reduce loads. On the other hand, the micropore size of PET foam materials will passivate the tips of the silver streaks inside the material, preventing the silver streaks from expanding under stress to form large cracks, thereby improving the load resistance of the blades. Summary of the invention

[0003] The object of the present invention is to provide a fine-pore supercritical foamed PET material and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] A fine-pore supercritical foamed PET material is made of the following raw materials in parts by weight: PET: 60-100 parts, organic nucleating agent: 0.5-5 parts; nano-nucleating agent: 0.1-0.5 parts; surfactant: 0.2-1 parts; crystallization accelerator: 0.5-1 parts; antioxidant: 0.5-5 parts; chain extender: 0.5-5 parts; foaming agent: 0.5-5 parts;

[0006] The foaming agent is a mixture of supercritical carbon dioxide and an alkane foaming agent, and is injected into a PET mixed melt formed by PET, an organic nucleating agent, a nano nucleating agent, a surfactant, a crystallization accelerator, an antioxidant, and a chain extender through multi-stage injection;

[0007] The mass of the alkane foaming agent is 50%-90% of the total mass of the foaming agent; the mass of the supercritical carbon dioxide is 10%-50% of the total mass of the foaming agent;

[0008] The screw of the twin-screw extrusion section is provided with a forward thread, and the twin-screw extrusion section includes a feeding section and a melt extrusion section. The thread pitch size of the melt extrusion section is set from dense to sparse, so as to ensure that the nano-nucleating agent is fully mixed in the PET melt to form a uniform small-sized crystal region; at the same time, it can avoid the problem of high PET crystallinity and low foaming ratio of the final product caused by the long saturation time of supercritical CO2 in the PET melt;

[0009] Preferably, the nano nucleating agent is a mixture of one or more of MgO, SiO2 and TiO, with a particle size of 10-100 nm. Before use, it needs to be modified with anhydrous ethanol and a silane coupling agent and dried.

[0010] Preferably, the crystallization accelerator is Surlyn resin, AClyn resin or a mixture of the two; and the surfactant is polyethylene glycol.

[0011] Preferably, the antioxidant is any one of antioxidant 1010, antioxidant 126, antioxidant 330, antioxidant 1098 and antioxidant H318, or a mixture of any two or more thereof in any ratio;

[0012] The chain extender is a mixture of an epoxy chain extender ADR and an acid anhydride chain extender PMDA.

[0013] Preferably, the organic nucleating agent is any one of aliphatic long carbon chain saturated carboxylic acid salts; sodium salt, potassium salt, calcium salt of monocarboxylic acid; sodium salt, potassium salt, calcium salt of benzoic acid; aromatic hydroxy sulfonate; magnesium salt, zinc salt of organic phosphorus compound and high molecular ion polymer.

[0014] The present invention also discloses a method for preparing a fine-pore supercritical foamed PET material, comprising the following steps:

[0015] S1, weighing PET, organic nucleating agent, nano nucleating agent, surfactant, crystallization accelerator, antioxidant and chain extender by weight, fully drying and mixing and stirring in a mixer to obtain a mixture;

[0016] S2, putting the mixed material obtained in step S1 into an extrusion foaming device for heating and melting to obtain a PET mixed melt, and then extruding and foaming the mixed material after adding a foaming agent in multiple stages to obtain a fine-pore supercritical foamed PET material with a pore diameter of 150-250 μm;

[0017] The extrusion foaming equipment comprises a twin-screw extrusion section and a single-screw conveying section arranged after the twin-screw extrusion section, the screw of the twin-screw extrusion section is provided with a forward thread, the twin-screw extrusion section comprises a feeding section and a melting extrusion section, the thread pitch size of the melting extrusion section is arranged from dense to sparse, the temperature of the twin-screw extrusion section is 180-265°C, and the temperature is graded from low to high and then to low along the material conveying direction.

[0018] Preferably, the weight ratios of the foaming agent filling amounts at the first foaming agent filling port, the second foaming agent filling port and the third foaming agent filling port are 2:3:5 respectively.

[0019] Specifically, the twin-screw extrusion section is divided into 8 temperature control zones from the feed port to the discharge end, namely zones one to eight, and the temperatures are set to 180°C, 250°C, 265°C, 260°C, 255°C, 255°C, 255°C, and 255°C, respectively; the first foaming agent filling port is set in zone three, the second foaming agent filling port is set in zone five, and the third foaming agent filling port is set in zone seven.

[0020] In order to ensure that the PET mixed melt and the foaming agent are fully mixed, the twin screws used in the twin screw extrusion section are respectively provided with reverse thread sections in the third and fifth temperature control zones.

[0021] Effective effect: The present invention adopts a mixed ingredient of an organic nucleating agent, a nano nucleating agent, a surfactant, and a crystallization accelerator, combined with a multi-stage filling method of a foaming agent. On the one hand, low-temperature mixing of the foaming agent and the nucleating agent can be achieved, thereby avoiding the problems of uneven dissolution of the foaming agent, low melt viscosity, slow crystallization rate, slow shaping rate of the pores, etc. in high-temperature processing; on the other hand, a large number of small-sized crystal regions can be formed in the PET mixed melt as heterogeneous nucleation points of bubbles, and finally a fine-pored PET foam material can be obtained.

[0022] Compared with the traditional simple organic nucleating agent, the nano nucleating agent has the characteristics of wide processing temperature window, small particle diameter, large specific surface area, stable chemical properties, etc. It can be evenly mixed and distributed in the PET matrix, providing a large number of crystal nuclei for PET crystallization, and finally forming a large number of small-sized crystal regions, improving the mechanical properties of PET; a large number of small-sized crystal regions serve as heterogeneous nucleation points of bubbles, reducing the nucleation energy barrier of critical bubble nuclei, increasing the nucleation rate and number of bubbles, increasing the number of pores in the matrix, and the presence of small-sized crystal regions can prevent the further growth and merging of pores, so that the pore size is refined. At the same time, a multi-stage foaming agent injection method is adopted in the twin-screw extrusion section, which can avoid the problem of high PET crystallinity and low foaming ratio of the final product caused by the long saturation time of supercritical CO2 in the PET melt, and finally the fine-porous PET foaming material prepared has high closed-cell rate, good mechanical properties, small pore size, and a pore diameter of 150-250μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is an electron microscope image of the foam interface of a conventional product.

[0024] Figure 2 This is an electron microscope image of the foam interface of the PET foam material prepared in Example 2.

[0025] Figure 3 It is a schematic structural diagram of the extrusion foaming equipment of the present invention. DETAILED DESCRIPTION

[0026] A fine-pore supercritical foamed PET material is made of the following raw materials in parts by weight: PET: 60-100 parts, organic nucleating agent: 0.5-5 parts; nano-nucleating agent: 0.1-0.5 parts; surfactant: 0.2-1 parts; crystallization accelerator: 0.5-1 parts; antioxidant: 0.5-5 parts; chain extender: 0.5-5 parts; foaming agent: 0.5-5 parts;

[0027] The foaming agent is a mixture of supercritical carbon dioxide and an alkane foaming agent, and is injected into a PET mixed melt formed by PET, an organic nucleating agent, a nano nucleating agent, a surfactant, a crystallization accelerator, an antioxidant, and a chain extender in a multi-stage injection manner with a set concentration gradient;

[0028] The mass of the alkane foaming agent is 50%-90% of the total mass of the foaming agent; the mass of the supercritical carbon dioxide is 10%-50% of the total mass of the foaming agent;

[0029] The concentration of the foaming agent is gradually increased from the feeding end to the end of the melt extrusion section, and the screw threads of the melt extrusion section are set from dense to sparse to ensure that the nano-nucleating agent is fully mixed in the PET melt to form a uniform small-sized crystal area; at the same time, it avoids the problem of high PET crystallinity and low foaming ratio of the final product caused by the long saturation time of supercritical CO2 in the PET melt.

[0030] The nano nucleating agent is a mixture of one or more of MgO, SiO2 and TiO, with a particle size of 10-100 nm. Before use, it needs to be modified with anhydrous ethanol and a silane coupling agent and dried.

[0031] By adopting the above technical scheme, compared with the traditional organic nucleating agent, the nano nucleating agent represented by MgO, SiO2 and TiO has the characteristics of wide processing temperature window, small particle diameter, large specific surface area, stable chemical properties, etc., can be evenly mixed and distributed in the PET matrix, provide a large number of crystal nuclei for PET crystallization, and finally form a large number of small-sized crystal regions, which improves the mechanical properties of PET; a large number of small-sized crystal regions serve as heterogeneous nucleation points of bubbles, reduce the nucleation energy barrier of critical bubble nuclei, increase the nucleation rate and number of bubbles, increase the number of pores in the matrix, and the presence of small-sized crystal regions can prevent the further growth and merging of pores, so that the pore size is refined. At the same time, a multi-stage foaming agent injection method is adopted in the twin-screw extrusion section, which can avoid the problem of high PET crystallinity and low foaming ratio of the final product caused by the long saturation time of supercritical CO2 in the PET melt, and finally the fine-porous PET foaming material prepared has high closed-cell rate, good mechanical properties, small pore size, and pore diameter of 150-250μm.

[0032] Wherein, the crystallization accelerator is one of Surlyn resin and AClyn resin or a mixture of the two; and the surfactant is polyethylene glycol.

[0033] Among them, the organic nucleating agent is any one of aliphatic long carbon chain saturated carboxylate; sodium salt, potassium salt, calcium salt of monocarboxylic acid; sodium salt, potassium salt, calcium salt of benzoic acid; aromatic hydroxy sulfonate; magnesium salt, zinc salt and high molecular ion polymer of organic phosphorus compound; the antioxidant is any one of antioxidant 1010, antioxidant 126, antioxidant 330, antioxidant 1098 and antioxidant H318, or a mixture of any two or more in any proportion; the chain extender is a mixture of epoxy chain extender ADR and anhydride chain extender PMDA.

[0034] The preparation method of the above-mentioned fine-pore supercritical foamed PET material comprises the following steps:

[0035] S1, weighing PET, organic nucleating agent, nano nucleating agent, surfactant, crystallization accelerator, antioxidant and chain extender by weight, fully drying and mixing and stirring in a mixer to obtain a mixture;

[0036] S2. The mixed material obtained in step S1 is put into an extrusion foaming device for heating and melting to obtain a PET mixed melt, and then a foaming agent is added in multiple stages for extrusion and foaming molding to obtain a fine-pore supercritical foamed PET material, wherein the pore diameter of the obtained PET material is 150-250 μm.

[0037] The extrusion foaming equipment includes a twin-screw extrusion section A and a single-screw conveying section B arranged after the twin-screw extrusion section A, the screw of the twin-screw extrusion section A is provided with a forward thread, the twin-screw extrusion section A includes a feed section and a melt extrusion section located after the feed section, and a feed port 40 is arranged above the feed section. The thread pitch of the melt extrusion section is set from dense to sparse. The temperature of the twin-screw extrusion section A is 180-265°C, and the temperature is graded from low to high and then to low along the material conveying direction. Specifically, the twin-screw extrusion section A is divided into 8 temperature control zones from the feed port 44 to the discharge end, which are one to eight zones, marked as 1, 2, 3,... 8 in sequence, and the temperatures are set to 180°C, 250°C, 265°C, 260°C, 255°C, 255°C, 255°C, 255°C, respectively.

[0038] The extrusion foaming equipment is provided with three foaming agent filling ports at intervals, which are the first foaming agent filling port 10, the second foaming agent filling port 20 and the third foaming agent filling port 30 in the material conveying direction, and the weight ratio of the foaming agent filling amount at the first foaming agent filling port, the second foaming agent filling port and the third foaming agent filling port is 2:3:5 respectively. The first foaming agent filling port 10 is arranged at the rear section of the third zone 3, the second foaming agent filling port 20 is arranged at the rear section of the fifth zone 5, and the third foaming agent filling port 30 is arranged at the rear section of the seventh zone 7. In order to ensure that the PET mixed melt and the foaming agent are fully mixed, the twin screw 9 used in the twin screw extrusion section A is provided with a reverse thread section 91 at the front end of the temperature control third zone 3 and the fifth zone 5, respectively, and the reverse thread section 91 is used to ensure that the PET mixed melt and the foaming agent are fully mixed.

[0039] The purpose of adopting temperature zoning control in the present invention is that: temperature zone 1 to temperature zone 3 are feeding and mixing sections, temperature zone 3 is provided with a foaming agent filling port 1, and the temperatures of temperature zones 1 to temperature zone 3 are set to 180°C, 250°C, and 265°C; because the nano nucleating agent has the characteristics of a wide processing temperature window, a small particle diameter, a large specific surface area, stable chemical properties, etc., the raw materials can be fed and mixed at a lower temperature, thereby avoiding decomposition and adhesion of the raw materials due to high temperature; at the same time, the mixing section is provided with a reverse thread at the front screw position of the foaming agent filling port 1, which has a sealing effect on the foaming agent injection port and enhances the mixing effect on the PET mixed melt, ensuring that the organic nucleating agent, the nano nucleating agent, the surfactant, and the crystallization accelerator can be uniformly mixed and distributed in the PET matrix to form a large number of small-sized crystal areas; the foaming agent multi-stage filling is adopted to control the foaming agent concentration in the feeding and mixing section, thereby avoiding induced crystallization caused by a long supercritical carbon dioxide saturation time.

[0040] Temperature zone four to temperature zone eight are the melting foaming sections, temperature zone five and temperature zone seven are respectively provided with foaming agent filling port two and foaming agent filling port three, and the temperatures of temperature zone four to temperature zone eight are set to 260°C, 255°C, 255°C, 255°C, 255°C; with the increase of the gradient of foaming agent concentration, on the one hand, the foaming agent composed of supercritical carbon dioxide and alkane foaming agent forms bubbles in the amorphous area with small-sized crystal areas as bubble heterogeneous nucleation points, which reduces the nucleation energy barrier of critical bubble nuclei, increases the bubble nucleation rate and the number of bubbles, and increases the number of bubbles in the matrix; on the other hand, in the bubble growth stage, the existence of small-sized crystal areas prevents the further growth and merging of bubbles, and the bubble size is refined; the surfactant reduces the surface energy of the PET resin melt, evens out the pressure difference between the inside and outside of the bubble, ensures the high solubility of the foaming agent in the foaming process, improves the disordered diffusion of foaming, and improves the bubble quality and closed cell rate.

[0041] Example 1

[0042] Based on the above preparation method, a fine-pore supercritical foamed PET material is prepared, comprising the following raw materials in parts by weight: PET: 90 parts, organic nucleating agent: 2 parts, nano-nucleating agent: 0.5 parts, surfactant: 0.5 parts, crystallization promoter: 0.5 parts, antioxidant: 0.5 parts, chain extender: 4 parts; and foaming agent: 2 parts.

[0043] In this embodiment, the organic nucleating agent is a saturated carboxylic acid salt of aliphatic long carbon chain; the nano nucleating agent is a mixture of SiO2 and MgO, with a particle size of 10-100nm, the weight of SiO2 is 40% of the total amount of the nano nucleating agent, and the weight of MgO is 60% of the total amount of the nano nucleating agent; the surfactant is polyethylene glycol; the crystallization accelerator is Surlyn resin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 126, and the weight ratio of antioxidant 1010 to antioxidant 126 is 1:1; the chain extender is a mixture of epoxy chain extender ADR and anhydride chain extender PMDA, the mass of epoxy chain extender ADR is 35% of the total mass of the chain extender; the mass of anhydride chain extender PMDA is 65% of the total mass of the chain extender; the foaming agent is a mixture of supercritical carbon dioxide and an alkane foaming agent, the mass of the alkane foaming agent is 70% of the total mass of the foaming agent, and the mass of the supercritical carbon dioxide is 30% of the total mass of the foaming agent.

[0044] Example 2

[0045] Based on the above preparation method, a fine-pore supercritical foamed PET material is prepared, comprising the following raw materials in parts by weight: PET: 94 parts, organic nucleating agent: 1.2 parts, nano-nucleating agent: 0.2 parts, surfactant: 0.2 parts, crystallization promoter: 0.6 parts, antioxidant: 0.8 parts, chain extender: 1.5 parts; foaming agent: 2 parts.

[0046] In this embodiment, the organic nucleating agent is sodium salt, potassium salt or calcium salt of monocarboxylic acid; the nano nucleating agent is MgO with a particle size of 10-100 nm; the surfactant is polyethylene glycol; the crystallization accelerator is AClyn resin; the antioxidant is antioxidant 330; the chain extender is a mixture of epoxy chain extender ADR and anhydride chain extender PMDA, the mass of the epoxy chain extender ADR is 20% of the total mass of the chain extender; the mass of the anhydride chain extender PMDA is 80% of the total mass of the chain extender; the foaming agent is a mixture of supercritical carbon dioxide and alkane foaming agent, the mass of the alkane foaming agent is 65% of the total mass of the foaming agent, and the mass of the supercritical carbon dioxide is 35% of the total mass of the foaming agent.

[0047] Example 3

[0048] Based on the above preparation method, a fine-pore supercritical foamed PET material is prepared, comprising the following raw materials in parts by weight: PET: 60 parts, organic nucleating agent: 0.5 parts, nano-nucleating agent: 0.1 parts, surfactant: 0.2 parts, crystallization promoter: 0.5 parts, antioxidant: 0.5 parts, chain extender: 0.5 parts; foaming agent: 0.5 parts.

[0049] In this embodiment, the organic nucleating agent is sodium salt, potassium salt or calcium salt of benzoic acid; the nano nucleating agent is TiO with a particle size of 10-100 nm; the surfactant is polyethylene glycol; the crystallization accelerator is AClyn resin; the antioxidant is antioxidant 1098; the chain extender is anhydride type chain extender PMDA; the mass of the anhydride type chain extender PMDA is 100% of the total mass of the chain extender; the foaming agent is a mixture of supercritical carbon dioxide and an alkane foaming agent, the mass of the alkane foaming agent is 90% of the total mass of the foaming agent, and the mass of the supercritical carbon dioxide is 10% of the total mass of the foaming agent.

[0050] Example 4

[0051] Based on the above preparation method, a fine-pore supercritical foamed PET material is prepared, comprising the following raw materials in parts by weight: PET: 100 parts, organic nucleating agent: 5 parts, nano-nucleating agent: 0.5 parts, surfactant: 1 part, crystallization promoter: 1 part, antioxidant: 5 parts, chain extender: 5 parts; foaming agent: 5 parts.

[0052] In this embodiment, the organic nucleating agent is any one of the magnesium salt, zinc salt and high molecular ion polymer of the organic phosphorus compound; the nano nucleating agent is SiO2 with a particle size of 10-100nm; the surfactant is polyethylene glycol; the crystallization accelerator is a 1:1 mixture of Surlyn resin and AClyn resin; the antioxidant is a mixture of antioxidant 1098 and antioxidant H318, and the weight ratio of antioxidant 1098 to antioxidant H318 is 1:1; the chain extender is a mixture of epoxy chain extender ADR and anhydride chain extender PMDA, and the mass of epoxy chain extender ADR is 40% of the total mass of the chain extender; the mass of anhydride chain extender PMDA is 60% of the total mass of the chain extender; the foaming agent is a mixture of supercritical carbon dioxide and alkane foaming agent, the mass of the alkane foaming agent is 50% of the total mass of the foaming agent, and the mass of the supercritical carbon dioxide is 50% of the total mass of the foaming agent.

[0053] The detection means involved in the present invention meets the following standards:

[0054] (1) Density: According to ISO 845 standard, the embodiment and the conventional product (i.e., conventional PET foam material, i.e., PET foam material without adding nano nucleating agent, surfactant and crystallization accelerator) were tested;

[0055] (2) Closed-cell ratio: According to GB / T 10799-2008, the embodiment and conventional products were tested;

[0056] (3) Compression strength: According to ISO 844 standard, the embodiment and conventional products were tested;

[0057] (4) Shear strength: The embodiment and conventional products were tested according to ASTM C273 standard;

[0058] (5) Tensile strength: According to ASTM C297 standard, the embodiment and conventional products were tested;

[0059] Density, compression strength, shear strength, tensile strength, closed porosity and average cell size were tested for Examples 1-4 and conventional products (10 samples were tested for each example, and one highest and one lowest value were removed to retain interval data for the remaining values). The test results are shown in Table 1:

[0060] Table 1 Comparison of test results of embodiment and conventional product

[0061]

[0062] For foamed PET materials, the apparent density and pore size of the material are intuitive indicators for measuring the lightweight and mechanical properties of PET foamed materials. The mechanical properties of the foamed material increase with the increase of the apparent density; the physical and mechanical properties increase with the increase of the closed cell rate; the larger the pore size, the lower the physical and mechanical properties of the material. In Examples 1-4 of the present invention, a composite nucleation system of nano-nucleating agent, surfactant and crystallization promoter is used, and a multi-stage foaming agent injection process is adopted to form a large number of small-sized crystal regions in the PET mixed melt. While refining the pores, it avoids the problems of excessively high PET crystallinity caused by the long saturation time of supercritical CO2 in the PET melt, and low foaming ratio of the final product. The fine-pore high foaming ratio PET material finally prepared has a small pore size and a pore diameter of 150-250μm, which has good physical and mechanical properties compared with conventional products.

[0063] Comparative Example 1

[0064] On the basis of Example 1, a fine-pore supercritical foamed PET material is prepared by including the following raw materials in parts by weight: PET: 90 parts, organic nucleating agent: 2 parts, nano-nucleating agent: 0.5 parts, surfactant: 0 parts, crystallization promoter: 0.5 parts, antioxidant: 0.5 parts, chain extender: 4 parts; foaming agent: 2 parts.

[0065] In this comparative example, the organic nucleating agent is a saturated carboxylate of aliphatic long carbon chain; the nano-nucleating agent is a mixture of SiO2 and MgO, with a particle size of 10-100nm, the weight of SiO2 is 40% of the total amount of the nano-nucleating agent, and the weight of MgO is 60% of the total amount of the nano-nucleating agent; the crystallization accelerator is Surlyn resin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 126, and the weight ratio of antioxidant 1010 to antioxidant 126 is 1:1; the chain extender is a mixture of epoxy chain extender ADR and anhydride chain extender PMDA, the mass of epoxy chain extender ADR is 35% of the total mass of the chain extender; the mass of anhydride chain extender PMDA is 65% of the total mass of the chain extender; the blowing agent is a mixture of supercritical carbon dioxide and an alkane blowing agent, the mass of the alkane blowing agent is 70% of the total mass of the blowing agent, and the mass of the supercritical carbon dioxide is 30% of the total mass of the blowing agent.

[0066] Comparative Example 2: Based on Example 1, a fine-pore supercritical foamed PET material is prepared by the following raw materials in parts by weight: PET: 90 parts, organic nucleating agent: 2 parts, nano-nucleating agent: 0.5 parts, surfactant: 0.5 parts, crystallization promoter: 0 parts, antioxidant: 0.5 parts, chain extender: 4 parts; foaming agent: 2 parts.

[0067] In this comparative example, the organic nucleating agent is a saturated carboxylic acid salt of aliphatic long carbon chain; the nano-nucleating agent is a mixture of SiO2 and MgO, with a particle size of 10-100nm, the weight of SiO2 is 40% of the total amount of the nano-nucleating agent, and the weight of MgO is 60% of the total amount of the nano-nucleating agent; the surfactant is polyethylene glycol; the antioxidant is a mixture of antioxidant 1010 and antioxidant 126, and the weight ratio of antioxidant 1010 to antioxidant 126 is 1:1; the chain extender is a mixture of epoxy chain extender ADR and anhydride chain extender PMDA, the mass of epoxy chain extender ADR is 35% of the total mass of the chain extender; the mass of anhydride chain extender PMDA is 65% of the total mass of the chain extender; the blowing agent is a mixture of supercritical carbon dioxide and an alkane blowing agent, the mass of the alkane blowing agent is 70% of the total mass of the blowing agent, and the mass of the supercritical carbon dioxide is 30% of the total mass of the blowing agent.

[0068] Comparative Example 3: Based on Example 1, a fine-pore supercritical foamed PET material is prepared by the following raw materials in parts by weight: PET: 90 parts, organic nucleating agent: 2 parts, nano-nucleating agent: 0.5 parts, surfactant: 0 parts, crystallization promoter: 0 parts, antioxidant: 0.5 parts, chain extender: 4 parts; foaming agent: 2 parts.

[0069] In this comparative example, the organic nucleating agent is a saturated carboxylate of aliphatic long carbon chain; the nano-nucleating agent is a mixture of SiO2 and MgO, with a particle size of 10-100nm, the weight of SiO2 is 40% of the total amount of the nano-nucleating agent, and the weight of MgO is 60% of the total amount of the nano-nucleating agent; the antioxidant is a mixture of antioxidant 1010 and antioxidant 126, and the weight ratio of antioxidant 1010 to antioxidant 126 is 1:1; the chain extender is a mixture of epoxy chain extender ADR and anhydride chain extender PMDA, the mass of epoxy chain extender ADR is 35% of the total mass of the chain extender; the mass of anhydride chain extender PMDA is 65% of the total mass of the chain extender; the blowing agent is a mixture of supercritical carbon dioxide and an alkane blowing agent, the mass of the alkane blowing agent is 70% of the total mass of the blowing agent, and the mass of the supercritical carbon dioxide is 30% of the total mass of the blowing agent.

[0070] Example 1 and Comparative Examples 1-3 (Comparative Examples 1-3 were respectively not added with one or two of the surfactant and the crystallization accelerator) and conventional products were tested for density, compressive strength, shear strength, tensile strength, closed porosity and cell size (each comparative example was tested for 10 times, one highest and one lowest value were removed, and the interval data of the remaining values ​​were retained for evidence), and the test results are shown in Table 2:

[0071] Table 2 Comparison of test results of embodiments, comparative examples and conventional products

[0072]

[0073] It can be seen from the above table that Example 1 of the present invention has a higher closed cell rate than the test data of Comparative Examples 1-3 and conventional products, that is, the composite nucleation system using a nano-nucleating agent, a surfactant and a crystallization promoter can make the foaming material have a higher closed cell rate and higher mechanical and physical properties; on the one hand, the higher closed cell rate enables the foaming material to have a more complete pore structure, which can reduce the absorption of resin during the subsequent processing of wind power products, reduce product weight, and achieve lightweight; on the other hand, the smaller average pore size will passivate the tips of the silver streaks inside the material, prevent the silver streaks from expanding under stress to form large cracks, and improve the product's load resistance.

[0074] See also Figure 1-Figure 2 , are all electron microscope images after magnification of 60x, and the upper left corner of the figure is a 1mm ruler. It can be seen from the electron microscope images of the foam interface corresponding to Example 1 and the conventional product that the sample pores of Example 1 are fine and uniform, and the average size is smaller than that of the conventional product. This shows that the mixed ingredients of the combination of organic nucleating agent, nano-nucleating agent, surfactant, and crystallization accelerator used in the present invention, combined with the multi-stage injection method of the foaming agent, can prepare a lightweight and mechanically excellent fine-pore supercritical foamed PET material.

[0075] The above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A fine-pore supercritical foamed PET material, characterized by: The invention is prepared from the following raw materials in parts by weight: PET: 60-100 parts, organic nucleating agent: 0.5-5 parts, nano nucleating agent: 0.1-0.5 parts, surfactant: 0.2-1 parts; Crystallization accelerator: 0.5-1 parts; Antioxidant: 0.5-5 parts; Chain extender: 0.5-5 parts; Foaming agent: 0.5-5 parts; The foaming agent is prepared by mixing supercritical carbon dioxide and an alkane foaming agent, and is injected into a PET mixed melt formed by PET, an organic nucleating agent, a nano-nucleating agent, a surfactant, a crystallization accelerator, an antioxidant, and a chain extender through multi-stage injection; The foaming agent concentration is gradually increased along the material conveying direction in the melt extrusion section, and the screw threads of the melt extrusion section are arranged from dense to sparse to ensure that the nano nucleating agent is fully mixed in the PET melt to form uniform small-sized crystal areas; The nano nucleating agent is a mixture of one or more of MgO, SiO2 and TiO, with a particle size of 10-100 nm. Before use, it needs to be modified with anhydrous ethanol and a silane coupling agent and dried.

2. The fine-pore supercritical foamed PET material according to claim 1, characterized in that: The crystallization accelerator is one of Surlyn resin and AClyn resin or a mixture of the two; the surfactant is polyethylene glycol.

3. The fine-pore supercritical foamed PET material according to claim 1, characterized in that: The antioxidant is any one of antioxidant 1010, antioxidant 126, antioxidant 330, antioxidant 1098 and antioxidant H318, or a mixture of any two or more thereof in any ratio; The chain extender is a mixture of epoxy chain extender ADR and acid anhydride chain extender PMDA.

4. The fine-pore supercritical foamed PET material according to claim 1, characterized in that: The organic nucleating agent is any one of aliphatic long carbon chain saturated carboxylate; sodium salt, potassium salt, calcium salt of monocarboxylic acid; sodium salt, potassium salt, calcium salt of benzoic acid; aromatic hydroxy sulfonate; magnesium salt, zinc salt of organic phosphorus compound and high molecular ion polymer.

5. A method for preparing a fine-pore supercritical foamed PET material according to any one of claims 1 to 4, characterized in that: The steps include: S1. Weigh PET, an organic nucleating agent, a nano-nucleating agent, a surfactant, a crystallization accelerator, an antioxidant, and a chain extender in parts by weight, dry them thoroughly, and mix and stir them in a blender to obtain a mixture; S2, putting the mixed material obtained in step S1 into an extrusion foaming device for heating and melting to obtain a PET mixed melt, and then extruding and foaming the melt after adding a foaming agent in multiple stages to obtain a fine-pore supercritical foamed PET material with a pore diameter of 150-250 μm; The extrusion foaming equipment includes a twin-screw extrusion section and a single-screw conveying section arranged after the twin-screw extrusion section. The screw of the twin-screw extrusion section is provided with a forward thread. The twin-screw extrusion section includes a feeding section and a melt extrusion section. The thread pitch of the melt extrusion section is arranged from dense to sparse. The temperature of the twin-screw extrusion section is 180-265°C, and the temperature is graded from low to high and then to low along the material conveying direction.

6. The method for preparing a fine-pore supercritical foamed PET material according to claim 5, wherein: The extrusion foaming equipment is provided with three foaming agent filling ports at intervals, which are the first foaming agent filling port 10, the second foaming agent filling port 20 and the third foaming agent filling port 30 in sequence along the material conveying direction. The weight ratio of the foaming agent filling amount at the first foaming agent filling port, the second foaming agent filling port and the third foaming agent filling port is 2:3:5 respectively.

7. The method for preparing a fine-pore supercritical foamed PET material according to claim 5, wherein: The twin-screw extrusion section is divided into 8 temperature control zones from the feed inlet to the discharge end, namely zones one to eight, and the temperatures are set to 180°C, 250°C, 265°C, 260°C, 255°C, 255°C, 255°C, and 255°C respectively.

8. The method for preparing a fine-pore supercritical foamed PET material according to claim 7, wherein: The first foaming agent filling port is set in the third zone, the second foaming agent filling port is set in the fifth zone, and the third foaming agent filling port is set in the seventh zone.

9. The method for preparing a fine-pore supercritical foamed PET material according to claim 7, wherein: The twin screws used in the twin screw extrusion section are respectively provided with reverse thread sections in the third and fifth temperature control zones to ensure that the PET mixed melt and the foaming agent are fully mixed.

Citation Information

Cited By

  • PET foamed material with composite modified structure and preparation method thereof

    CN122852102A